Could JC virus be involved in the onset of multiple system atrophy? A hypothesis. (April 2023) - Linard, Morgane; Foubert-Samier, Alexandra; Pacaud, Jordi; Helmer, Catherine
Highlights: The Authors hypothesize that JC virus (JCV) may be implicated in the onset of multiple system atrophy (MSA). JCV DNA was reported in the brain of some immunocompetent subjects, mainly in oligodendrocytes. Infections can trigger α-synuclein accumulation, a potential antimicrobial peptide. JCV may be implicated in the onset of early neurogenic urinary symptoms in MSA. The onset of MSA may require the presence of specific susceptibility factors.